2017
DOI: 10.1155/2017/2734976
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Oxidative Stress, Cell Cycle Arrest, and Mitochondrial Apoptosis after Combined Treatment of Hepatocarcinoma Cells with Maleic Anhydride Derivatives and Quercetin

Abstract: The inflammatory condition of malignant tumors continually exposes cancer cells to reactive oxygen species, an oxidizing condition that leads to the activation of the antioxidant defense system. A similar activation occurs with glutathione production. This oxidant condition enables tumor cells to maintain the energy required for growth, proliferation, and evasion of cell death. The objective of the present study was to determine the effect on hepatocellular carcinoma cells of a combination treatment with malei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Jeon et al reported an increase in p53 levels and a decrease in cyclin A and checkpoint kinase 1 (CHK1) expression in HepG2 cells after quercetin treatment [25], while this drug downregulated p53 and enhanced G0/G1 and G2/M populations in HepG2 and HuH7 HCC lines [51]. Augmented levels of p21 and p27, cell cycle inhibitors, and cyclin D1 reduction were observed in another study with HepG2 cells [33] and it has been also shown that quercetin promoted G0/G1-phase arrest [49,52,53] through upregulating p16, p21 and p53 [53]. Conversely, a cell cycle arrest at G2/M phase has been described as a quercetin effect against HCC cell proliferation in HepG2 [30] and LM3 liver cancer lines [22].…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 90%
See 4 more Smart Citations
“…Jeon et al reported an increase in p53 levels and a decrease in cyclin A and checkpoint kinase 1 (CHK1) expression in HepG2 cells after quercetin treatment [25], while this drug downregulated p53 and enhanced G0/G1 and G2/M populations in HepG2 and HuH7 HCC lines [51]. Augmented levels of p21 and p27, cell cycle inhibitors, and cyclin D1 reduction were observed in another study with HepG2 cells [33] and it has been also shown that quercetin promoted G0/G1-phase arrest [49,52,53] through upregulating p16, p21 and p53 [53]. Conversely, a cell cycle arrest at G2/M phase has been described as a quercetin effect against HCC cell proliferation in HepG2 [30] and LM3 liver cancer lines [22].…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 90%
“…Quercetin antitumor effects have been described in different cancer types, including HCC [1]. In 25 of the articles included in the present review, quercetin efficacy as single treatment was evaluated employing different HCC study models [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46,48,49,[51][52][53][54]57]. Antiproliferative effect of this flavonoid alone has been demonstrated in several researches with in vitro models [22][23][24][25][26][27][30][31][32][33]35,38,46,48,49,[51][52][53][54], highlighting the HepG2 cell line as the most used in 21 of the 25 articles [24,25,<...>…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 99%
See 3 more Smart Citations